Enhanced Nanofiltration Process of Thin Film Composite Membrane Using Dodecyl Phenol Ethoxylate and Oleic Acid Ethoxylate for Oilfield Calcite Scale Control - Saedah R. Al-Mhyawi (MDPI AG, 2021)
This research studied the enhancing effect on the nanofiltration composite (TFCNF) membrane of two non-ionic surfactants on a thin-film composite nanofiltration membrane (TFCNF) for calcite scale (CaCO3) inhibition in oilfield application to develop a multifunctional filtration system: nanofiltration, antiscalant, and scale inhibitors. The effectiveness of dodecyl phenol ethoxylate (DPE) and oleic acid ethoxylate (OAE) as novel scale inhibitors were studied using the dynamic method. Scaling tests on the membrane were performed to measure the scaling of the inhibited membrane with and without scale inhibitors for salt rejection, permeability, and flux decline. The results revealed that the TFCNF membrane flux decline was improved in the presence of scale inhibitors from 22% to about 15%. The rejection of the membrane scales increases from 72% for blank membranes, reaching 97.2% and 88% for both DPE and OAE, respectively. These confirmed that scale inhibitor DPE had superior anti-scaling properties against calcite deposits on TFCNF membranes. Inhibited scaled TFCNF membrane was characterized using environmental scanning electron (ESEM), FTIR, and XRD techniques. The results of the prepared TFCNF membrane extensively scaled by the calcite deposits were correlated to its morphology.